Pelatihan Komunikasi Aparat Desa Dalam Menjalankan Pemerintahan Desa : . - Ari Sulistyanto; Tabrani Syahrizal; Yudhistira Ardi Poetra; Pagi Muhamad; Dinar Sulistyowati (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2026)
Communication is a strategic element in supporting the effectiveness of participatory and accountable village governance. However, several issues remain, including the low interpersonal communication skills of village officials, weak internal coordination, and the suboptimal use of digital communication technologies. Therefore, this activity aims to enhance the communication competencies of village apparatus through systematically and applicatively designed training. The methods employed include lectures, discussions, and practical simulations of governmental communication. The training materials cover understanding public service communication at the village level, interpersonal communication and internal coordination, the use of village communication media (e.g., WhatsApp, village websites, social media), public message formulation and information management, and simulations of public service communication with citizens. Participants consisted of village heads, secretaries, hamlet heads, neighborhood leaders (RT/RW), and public service staff. Evaluation results show a significant improvement in participants’ communication understanding and skills, with an average increase from 48.2% before training to 81.4% after training. Village officials became more skilled in delivering information, utilizing digital media, and engaging in empathetic and effective communication with the community. These findings affirm that enhancing communication capacity is a key component in building responsive, transparent, and participatory village governance, in line with good governance principles in local development. Furthermore, the training encouraged officials to become more adaptive in conveying information efficiently and promptly.